Cultural Capital as Performance: Tote Bags and Contemporary Literary Festivals - Dane, Alexandra (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2020)
The canvas tote bag, often branded with the name and logo of a popular cultural institution or bookstore, has become a shorthand for an individual’s accumulated cultural capital; this seemingly innocuous accessory has the power to signal to one’s peers the level of their engagement with the cultural and creative industries in a seemingly casual but deeply coded manner. The literary festival presents the perfect opportunity for individuals to signal to those around them that they, for example, subscribe to the New Yorker or donate money to the V&A museum. This article presents the findings of an observational study conducted at four literary festivals in Australia, the United Kingdom and the United States. Four distinct categories emerged from this analysis of tote bags carried at literary festivals: the festival tote that is sold at the festival; totes associated with cultural institutions; totes with political, satirical or ironic slogans; totes that are not associated with any particular arts or cultural brand or institution. I argue that, especially where the first three categories are concerned, the tote bags carried at literary festivals are consciously chosen for the purpose of signalling one’s cultural capital.